Primary Sources and Asian Pasts - Amy Paris, Langenberg; Bisschop, Peter Christiaan; Bryan J., Cuevas; Cecil, Elizabeth A.; Csaba, Dezső; Elizabeth A., Cecil; Emmanuel, Francis; Hans T., Bakker; James L., Fitzgerald; Janice, Stargardt; Laxshmi Rose, Greaves; Max, Deeg; et al. (2020)
This conference volume unites a wide range of scholars working in the fields of history, archaeology, religion, art, and philology in an effort to explore new perspectives and methods in the study of primary sources from premodern South and Southeast Asia. The contributions engage with primary sources (including texts, images, material artefacts, monuments, as well as archaeological sites and landscapes) and draw needed attention to highly adaptable, innovative, and dynamic modes of cultural production within traditional idioms. The volume works to develop categories of historical analysis that cross disciplinary boundaries and represent a wide variety of methodological concerns. By revisiting premodern sources, Asia Beyond Boundaries also addresses critical issues of temporality and periodization that attend established categories in Asian Studies, such as the "Classical Age" or the "Gupta Period". This volume represents the culmination of the European Research Council (ERC) Synergy project Asia Beyond Boundaries: Religion, Region, Language and the State, a research consortium of the British Museum, the British Library and the School of Oriental and African Studies, in partnership with Leiden University.